2015
DOI: 10.1590/s1516-89132015060366
|View full text |Cite
|
Sign up to set email alerts
|

Microencapsulation and Storage Stability of Lycopene Extracted from Tomato Processing Waste

Abstract: The aim of this study was to optimize the encapsulation of lycopene using response surface methodology and to determine its stability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 19 publications
0
6
0
3
Order By: Relevance
“…Rodrigues-Huezo et al (51) reported values for encapsulation efficiency between 25.6 and 87.5% for encapsulates obtained by spray drying of emulsions containing carotenoids using gum arabic, gellan gum and maltodextrin as encapsulation materials (49). In the study of Ranveer et al (52) the effect of different process parameters, core to wall ratio, sucrose to gelatin and inlet temperature on encapsulation yield and encapsulation efficiency of lycopene in encapsulates obtained by spray-drying technique were investigated. Highest encapsulation efficiency (92.6 %) and encapsulation yield (82.2%) was observed when the core to wall ratio was 1:4, sucrose to gelatin ratio was 7:3 and inlet temperature was 180 °C (52).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rodrigues-Huezo et al (51) reported values for encapsulation efficiency between 25.6 and 87.5% for encapsulates obtained by spray drying of emulsions containing carotenoids using gum arabic, gellan gum and maltodextrin as encapsulation materials (49). In the study of Ranveer et al (52) the effect of different process parameters, core to wall ratio, sucrose to gelatin and inlet temperature on encapsulation yield and encapsulation efficiency of lycopene in encapsulates obtained by spray-drying technique were investigated. Highest encapsulation efficiency (92.6 %) and encapsulation yield (82.2%) was observed when the core to wall ratio was 1:4, sucrose to gelatin ratio was 7:3 and inlet temperature was 180 °C (52).…”
Section: Resultsmentioning
confidence: 99%
“…Among several strategies to protect carotenoids, encapsulation is one that has been often applied and was found to enhance the stability of carotenoids (12). The protective mechanism of encapsulation is to form a membrane (wall system) to enclose the droplets or particles of the encapsulated material (core) (13).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Ranveer et al . () reported that approximately 92.6% of the compounds were entrapped after spray‐drying in agreement with Rocha‐Selmi et al . (), who reported more than 90% EE using complex coacervation.…”
Section: Resultsmentioning
confidence: 99%
“…Na escolha da proporção dos materiais que integram a mistura física inicial, por não existirem pesquisas de uso do CH como biomaterial na formação de partículas, foram utilizadas como referência as pesquisas onde a gelatina tem sido usada como biomaterial carreador do licopeno mediante métodos convencionais (CHIU et al 2007;RANVEER et al 2015; ROCHA-SELMI; FÁVARO-TRINDADE; GROSSO, 2013;SHU et al 2006;SILVA et al 2012), pois a gelatina é um material de natureza similar ao CH.…”
Section: Preparo Da Mistura Física Inicialunclassified
“…Seu consumo tem sido promovido pois sua alta atividade antioxidante protege contra doenças influenciadas por reações de radicais livres, tais como o câncer de próstata, câncer de pâncreas, câncer de estomago, câncer de pele, e doenças cardiovasculares (KUN; LULE; XIAO-LIN, 2006;PERVEEN et al, 2015;SOARES et al, 2015). Porém, o licopeno é susceptível à isomerização e oxidação por fatores ambientais como a luz, temperatura e oxigênio, durante o processamento tecnológico e armazenamento (LEE;CHEN, 2002;RANVEER et al, 2015;SHI et al, 2002). Assim, uma maneira de protegê-lo, facilitar o uso como ingrediente e garantir sua presença e estabilidade nos produtos que o conterão (ROCHA; FÁVARO-TRINDADE; GROSSO, 2012) é mediante a formação de partículas em pó usando materiais carreadores biológicos de natureza polimérica (COCERO et al, 2009;ĐORĐEVIĆ et al, 2015; SALDAÑA; COIMBRA; CARDOZO-FILHO, 2015).…”
Section: Introductionunclassified